Metal bipolar plate and method of making and using same
By preparing a MxTiyN solid solution coating of group VB transition metal nitrides and titanium nitride on the bipolar plate of a titanium-based fuel cell, the corrosion problem of the titanium substrate in a strongly acidic environment was solved, the conductivity was maintained and the increase in contact resistance was prevented, and the stable operation of the fuel cell was achieved.
Patent Information
- Application Number
- CN202310776881.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-06-28
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2043-06-28
AI Technical Summary
Existing titanium-based fuel cell bipolar plates are prone to corrosion in strongly acidic environments, leading to increased through-holes and contact resistance, which affects current output and fuel cell stability. At the same time, the conductivity of existing coatings decreases after oxidation, making them unable to effectively prevent corrosion.
A composite protective layer of MxTiyN solid solution, composed of group VB transition metal nitrides and titanium nitride, is formed on the surface of titanium metal plate through sol-gel method and nitriding treatment. It has strong adhesion and can maintain a certain electrical conductivity after oxidation.
It achieves excellent electrical conductivity and corrosion resistance in highly acidic environments, avoids the formation of porous structures, and ensures stable operation and current output of fuel cells.
Smart Images

Figure CN116845268B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fuel cell technology, and in particular to metal bipolar plates, their preparation methods, and applications. Background Technology
[0002] In fuel cells, bipolar plates are one of the key components, used to separate hydrogen and oxygen, preventing gas permeation and forming a single-cell structure. They also collect and conduct current from a strongly acidic medium into the motor. Traditional metal bipolar plates typically use stainless steel as the substrate material. However, in practical use, stainless steel is prone to corrosion under the combined effects of strong acidic environments (H₂SO₄) and fluoride ions. This corrosion creates through-holes and releases metal cations such as aluminum, nickel, and chromium, which poison the catalyst and degrade the proton exchange membrane. Therefore, in recent years, corrosion-resistant titanium-based bipolar plates have gained increasing favor in academia and industry. This is because titanium passivates in corrosive environments, generating titanium dioxide to physically isolate the corrosive environment from the metal substrate, thus reducing subsequent corrosion. Moreover, even with the presence of fluoride ions, titanium dioxide can passivate the corrosive environment, forming titanium dioxide that physically isolates the metal substrate from the corrosive environment, reducing subsequent corrosion. - The titanium compounds produced by corrosion entering the fuel cell have not been shown to poison the catalyst or degrade the proton exchange membrane. However, on the downside, this passivation layer is a non-conductive oxide, leading to high contact resistance between the titanium-based bipolar plate and the gas diffusion layer. This hinders current output, generates additional heat, and is detrimental to the stable operation of the fuel cell.
[0003] To further improve the corrosion resistance of titanium-based bipolar plates and solve the problem of high contact resistance after operation, transition metal nitride or carbide coatings are typically prepared on the surface of the titanium plate. Among these, transition metal nitrides and carbides exhibit excellent resistance to acid corrosion due to the presence of metal-nitrogen / carbon covalent bonds. Furthermore, the valence electron bands of transition metal nitrides and carbides are half-filled, forming a conductive current under an external field, thus possessing excellent conductivity, typically above 10⁻⁶. 3 S / cm 2 -10 5 S / cm 2 More importantly, as a coating or protective layer, it generally does not experience the corrosion or peeling that occurs with carbon-based coatings during start-up and shutdown due to high-voltage surges, thus showing great promise.
[0004] Among these transition metal nitrides or carbides, titanium nitride (TiN) is a material with high thermal and chemical stability, and also possesses the highest electrical conductivity among transition metal nitrides, thus attracting widespread attention in the field of titanium-based bipolar plate manufacturing. However, titanium nitride has a drawback when used as a coating: the originally conductive titanium nitride layer will inevitably be oxidized into non-conductive titanium dioxide under the combined action of the anode and oxygen. Therefore, the contact resistance between the gas diffusion layer and the bipolar plate shows a continuously increasing trend, ultimately leading to a decrease in the overall performance of the fuel cell. Therefore, a redesign of the titanium nitride protective layer is needed to ensure that it retains a certain level of electrical conductivity even after oxidation to titanium dioxide.
[0005] In response, a method for increasing the electrical conductivity of titanium dioxide by doping it with high-valence niobium was published in the reference (Applied Physics Letters 86.25(2005):15-95.). The results showed that the electrical conductivity of titanium dioxide could be increased to a maximum of 10 at room temperature. 3 S / cm 2 Therefore, this mechanism can be used as a failure management method for titanium nitride coatings, ensuring that the titanium nitride coating still has a certain conductivity after inevitable anodizing.
[0006] Patent CN1953259A discloses a method for using Nb or Zr-doped titanium oxynitride as a coating for bipolar plates. This coating is obtained by high-temperature nitriding of a mixture of TiO2 / Nb2O5 or TiO2 / ZrO2 in H2 / N2. However, the reaction from oxide to nitride involves two processes, the first step of which involves a high-valence transition metal, such as Ti... 4+ Nb 5+ Ti was reduced to a low-priced state. 3+ Nb 3+ The oxygen atoms, some of which are covalently bonded to the oxide, are reduced by hydrogen to form water molecules that leave the oxide. However, this reduction in atomic numbers is not compensated for when nitrogen atoms participate in the nitriding reaction in the second step, resulting in a porous structure on the coating surface. This porous structure can lead to corrosion by corrosive agents in fuel cells, such as H2SO4 and F. - It can easily approach metal substrates, causing metal corrosion. Therefore, the patent does not disclose any convincing corrosion resistance data. Summary of the Invention
[0007] Therefore, it is necessary to provide a metal bipolar plate, its preparation method and application, which has excellent electrical conductivity and corrosion resistance, and can be processed continuously on a large scale.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is: a metal bipolar plate, comprising:
[0009] Titanium metal plate;
[0010] A composite protective layer is disposed on the surface of the titanium metal plate. The composite protective layer includes group VB transition metal nitrides and titanium nitride, and the group VB transition metal nitrides and titanium nitrides are doped with the chemical formula M. x Ti y The solid solution of N, where M represents a group VB transition metal element, and 0.01≤x≤0.15, 1.60≤y≤2.00.
[0011] In one embodiment, the group VB transition metal nitride is selected from at least one of vanadium nitride, niobium nitride, or tantalum nitride.
[0012] In one embodiment, the microstructure of the composite protective layer is crystalline.
[0013] In one embodiment, the titanium nitride is formed by the diffusion and reaction of titanium atoms in the titanium metal plate.
[0014] In one embodiment, the composite protective layer includes a bottom layer and a top layer, the bottom layer being located between the titanium metal plate and the top layer, and the mass fraction of the group VB transition metal nitride in the top layer being greater than the mass fraction in the bottom layer.
[0015] In one embodiment, the bottom layer is a titanium nitride layer, and the top layer is a doped layer of the group VB transition metal nitride and the titanium nitride.
[0016] In one embodiment, the thickness of the titanium metal plate is ≤0.5mm; and / or, the thickness of the composite protective layer is 0.4μm-1.5μm.
[0017] In the composite protective layer of the metal bipolar plate of this invention, due to the similarity in atomic radius and outer electron distribution, group VB transition metal nitrides and titanium nitride can be miscible in any proportion, forming a structure with the expression M. x Ti y The interstitial solid solution of N, during its formation, experiences a volume increase due to the increase in the number of atoms, causing potential micropores to be compressed and sealed. Therefore, the composite protective layer of this invention has a dense structure, which can physically isolate the titanium metal plate from the corrosive medium, achieving the purpose of corrosion protection; at the same time, this M x Ti yThe solid solution of nitrogen exhibits a synergistic effect, resulting in a resistivity that is more than 50% lower than that of titanium nitride or group VB transition metal nitrides when they exist alone. Consequently, the metal bipolar plate of this invention possesses excellent conductivity and corrosion resistance.
[0018] In addition, the composite protective layer of this invention has strong interfacial force and good bonding force with the titanium metal plate. Therefore, when applied to fuel cells, it is not easy to fall off under strong assembly force. More importantly, it can avoid the generation of completely non-conductive titanium dioxide in actual working conditions, thus achieving the purpose of failure management of the composite protective layer.
[0019] This invention also discloses a method for preparing the aforementioned metal bipolar plate, comprising the following steps:
[0020] Titanium metal plates are available;
[0021] A group VB transition metal oxide thin film is prepared on the surface of the titanium metal plate to obtain a preform;
[0022] The preform is nitrided at a temperature of 700℃-825℃ to obtain a metal bipolar plate.
[0023] In one embodiment, a group VB transition metal oxide film is prepared on the surface of the titanium metal plate by a sol-gel method, the thickness of the group VB transition metal oxide film being 0.1 μm-0.7 μm.
[0024] In one embodiment, the nitriding medium is a nitrogen-containing gas or a mixture of nitrogen-containing gas and a protective gas.
[0025] In one embodiment, the flow rate of the nitrogen-containing gas is 0.1 L / min to 1.0 L / min, and the pressure is 0.2 MPa to 0.5 MPa.
[0026] In one embodiment, the N-containing gas is selected from at least one of NH3 and N2.
[0027] In the nitriding process of this invention, both N atoms and Ti atoms in the titanium metal plate undergo free diffusion and reaction into the group VB transition metal oxide film. Therefore, for the preparation of the formula M... x Ti y The solid solution process of N involves a continuous increase in material. Furthermore, the combination of the fact that group VB transition metal nitrides and titanium nitride are miscible in any proportion ensures that the resulting composite protective layer exhibits a dense structure without porous structures. Moreover, the preparation process does not require a vacuum environment; the diffusion and reaction of Ti and N atoms occur simultaneously during the nitriding process, enabling large-scale continuous processing and improving production efficiency.
[0028] In addition, in the preparation method of the present invention, the temperature is as low as 700℃-825℃, which is a certain temperature difference from the α→β phase transformation temperature (882.5℃) of the titanium metal plate. Therefore, the titanium metal plate itself will not deform during the whole process, and the manufacturing of ultra-thin (<0.5mm) metal bipolar plates can be realized.
[0029] The present invention also discloses an application of the aforementioned metal bipolar plate in a fuel cell. Attached Figure Description
[0030] Figure 1 This is a cross-sectional structural schematic diagram of one embodiment of the metal bipolar plate of the present invention;
[0031] Figure 2 This is a cross-sectional structural schematic diagram of another embodiment of the metal bipolar plate of the present invention;
[0032] Figure 3 This is a scanning electron microscope image of the composite protective layer of sample 1 obtained in Example 1 of the present invention;
[0033] Figure 4 The results of scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) of the composite protective layer of sample 1 obtained in Example 1 of the present invention are shown.
[0034] Figure 5 The results of time-of-flight secondary ion mass spectrometry (TOF-SIMS) of the composite protective layer of sample 1 obtained in Example 1 of this invention;
[0035] Figure 6 This is a scanning electron microscope image of the composite protective layer obtained in Embodiment 2 of the present invention;
[0036] Figure 7 This is a scanning electron microscope image of the composite protective layer obtained in Embodiment 3 of the present invention.
[0037] In the diagram: 1. Titanium metal plate; 2. Composite protective layer; 21. Bottom layer; 22. Top layer. Detailed Implementation
[0038] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments or examples only and is not intended to limit the invention. The optional scope of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all related listed items.
[0040] like Figure 1 and Figure 2 As shown, the metal bipolar plate provided by the present invention includes a titanium metal plate 1 and a composite protective layer 2 disposed on the surface of the titanium metal plate 1. The composite protective layer 2 includes a group VB transition metal nitride and titanium nitride, and the group VB transition metal nitride and the titanium nitride are doped with a chemical formula M. x Ti y The solid solution of N, where M represents a group VB transition metal element, wherein 0.01≤x≤0.15, 1.60≤y≤2.00, and preferably 0.03≤x≤0.12, 1.62≤y≤1.86.
[0041] Among them, the group VB transition metal element is selected from at least one of V, Nb or Ta, and correspondingly, the group VB transition metal nitride includes at least one of vanadium nitride (VN), niobium nitride (NbN) or tantalum nitride (TaN), and titanium nitride includes TiN and Ti2N.
[0042] It should be noted that when performing elemental analysis using scanning electron microscopy and energy dispersive spectroscopy on the composite protective layer 2, the energy dispersive spectroscopy results showed only peaks for Ti, N, and group VB transition metals, but no peak for O. Therefore, there are no nitrogen oxides in the composite protective layer 2.
[0043] Due to the similarity in atomic radius and outer electron distribution, group VB transition metal nitrides and titanium nitrides can be miscible in any proportion and diffuse freely in the interlayer voids, constructing a structure expressed as M. x Ti y The interstitial solid solution of N eliminates micropores in its morphology. Therefore, the composite protective layer 2 of this invention has a dense structure and its microstructure exhibits a crystalline state, which can physically isolate the titanium metal plate from the corrosive medium, thereby achieving the purpose of corrosion prevention.
[0044] At the same time, this M x Ti yThe solid solution of nitrogen exhibits a synergistic effect, resulting in a resistivity that is more than 50% lower than that of titanium nitride or group VB transition metal nitrides when they exist alone. Consequently, the metal bipolar plate of this invention possesses excellent conductivity and corrosion resistance.
[0045] The composite protective layer 2 of the present invention has strong interfacial force and good bonding force with the titanium metal plate 1. In some embodiments, the titanium nitride in the composite protective layer 2 is formed by the diffusion and reaction of titanium atoms in the titanium metal plate. On the one hand, this is beneficial to further improve the bonding force between the composite protective layer 2 and the titanium metal plate 1. On the other hand, the titanium metal plate can be used directly, and it is beneficial to improve the density of the composite protective layer 2.
[0046] In some embodiments, the composite protective layer 2 includes a bottom layer 21 and a top layer 22, wherein the bottom layer 21 is located between the titanium metal plate 1 and the top layer 22, and the mass fraction of the group VB transition metal nitride in the top layer 22 is greater than the mass fraction in the bottom layer 21. Further, the bottom layer 21 is a titanium nitride layer, and the top layer 22 is a doped layer of the group VB transition metal nitride and the titanium nitride.
[0047] The present invention does not limit the titanium metal plate. Preferably, industrial grade titanium of TA1, TA2 or TC4 as specified in GB / T 3620.1-2016 is used as the material of titanium metal plate 1. The thickness of titanium metal plate 1 is ≤0.5mm, preferably ≤0.2mm.
[0048] In order to balance the anti-corrosion performance of the coating with the defects that may occur during the nitriding process, in some embodiments, the thickness of the composite protective layer 2 is 0.4μm-1.5μm, preferably 0.7μm-1.4μm.
[0049] In this invention, the composite protective layer 2 can be disposed on one side of the titanium metal plate 1, such as... Figure 1 As shown, it can also be set on both sides of the titanium metal plate 2, such as... Figure 2 As shown, you can choose the appropriate option based on your application needs.
[0050] This invention does not limit the preparation method of the composite protective layer 2. It can be prepared by vacuum coating methods such as PVD, CVD, and magnetron sputtering. However, the high vacuum environment required in vacuum coating makes the gas intake and exhaust process quite long, which restricts the production efficiency. At the same time, the purity requirements of the target material and raw materials are high, but they cannot be completely deposited onto the surface of the titanium metal plate during the evaporation process, resulting in low material utilization and increasing the cost of preparing the composite protective layer 2, which is not conducive to further commercialization.
[0051] In this regard, the present invention also provides a method for preparing the aforementioned metal bipolar plate, comprising the following steps:
[0052] S1, provides titanium metal plates;
[0053] S2, Prepare a group VB transition metal oxide film on the surface of the titanium metal plate to obtain a preform;
[0054] S3, the preform is nitrided at a temperature of 700℃-825℃ to obtain a metal bipolar plate.
[0055] In step S1, the titanium metal plate can also be pretreated to remove oil stains and oxide layers. The pretreatment can be carried out by pickling, washing with water and ultrasonic treatment or a combination of these methods.
[0056] In step S2, a group VB transition metal oxide film is prepared on the surface of the titanium metal plate using the sol-gel method. Specifically, this includes: first, preparing a compound solution containing group VB transition metal elements, such as a compound solution containing vanadium, niobium, or tantalum, which can be prepared using group VB transition metal chlorides or alkoxides such as vanadium trichloride, niobium pentachloride, or tantalum pentachloride as raw materials; second, applying the compound solution containing group VB transition metal elements to the surface of the titanium metal plate by methods such as impregnation or spraying, forming a layer of compound containing group VB transition metal elements on its surface, followed by drying and sintering to obtain a group VB transition metal oxide film. Preferably, the thickness of the group VB transition metal oxide film is 0.1 μm-0.7 μm.
[0057] In step S3, the nitriding medium is a nitrogen-containing gas or a mixture of nitrogen-containing gas and a protective gas. The flow rate of the nitrogen-containing gas is 0.1 L / min-1.0 L / min, and the pressure is 0.2 MPa-0.5 MPa. The nitrogen-containing gas is selected from at least one of NH3 and N2. The nitriding time can be adjusted according to the thickness of the group VB transition metal oxide film. Preferably, the nitriding temperature is 725℃-825℃, which helps to shorten the nitriding time.
[0058] During the nitriding process, N atoms and Ti atoms from the titanium metal plate will freely diffuse and react into the group VB transition metal oxide film to form titanium nitride and group VB transition metal nitrides. Therefore, for the preparation of the formula M... x Ti y The solid solution process of N is a process of continuous increase of matter. At the same time, the combination of the characteristics that group VB transition metal nitrides and titanium nitride can be miscible in any proportion ensures that the resulting composite protective layer will not have a porous structure in its microstructure and has a dense structure.
[0059] Therefore, the preparation method provided by the present invention adopts the sol-gel method combined with nitriding treatment. The preparation process does not require a vacuum environment. During the nitriding treatment, the diffusion and reaction of Ti atoms and N atoms are realized simultaneously. Therefore, it can be processed on a large scale and continuously, thus improving production efficiency.
[0060] Meanwhile, in the preparation method of the present invention, the temperature is as low as 700℃-825℃, which is a certain temperature difference from the α→β phase transformation temperature (882.5℃) of the titanium metal plate. Therefore, the titanium metal plate itself will not deform during the whole process, and the manufacturing of ultra-thin (<0.5mm) metal bipolar plates can be realized.
[0061] The present invention also provides an application of the metal bipolar plate in a fuel cell. When the metal bipolar plate is applied to a fuel cell, the composite protective layer 2 is not easy to fall off under strong assembly force. More importantly, it can avoid the generation of completely non-conductive titanium dioxide in actual working conditions, thus achieving the purpose of failure management of the composite protective layer 2.
[0062] The following specific embodiments will further illustrate the metal bipolar plate, its preparation method, and its application.
[0063] Example 1
[0064] First, place the flask in a prepared ice-water bath, then add 58.3 mL of anhydrous ethanol. While stirring magnetically, slowly add 5.5 g of niobium pentachloride (NbCl5) powder. Then, slowly raise the temperature to room temperature. After the NbCl5 and ethanol have reacted completely, slowly add 1.35 mL of deionized water and 0.33 mL of concentrated nitric acid (63% HNO3). After the addition is complete, gradually raise the temperature to 60°C and maintain the temperature under reflux for 3 hours to allow the materials to react completely, yielding a yellow, transparent liquid. Aging at room temperature for one day yields a 0.34 mol / L niobium ethoxylate (Nb(OCH2CH3)5) sol solution.
[0065] A 0.1mm thick titanium sheet made of TA1 grade industrial pure titanium was selected. First, the oil was removed by soaking in a surfactant solution at 90°C. Then, it was soaked in an acid solution (80% water + 5% hydrofluoric acid + 15% nitric acid by volume) at 30°C for 40 seconds to remove the titanium oxide layer on the surface of the titanium sheet caused by heat processing. Then, the ash generated by acid washing was removed by ultrasonication in water. Finally, it was rinsed with deionized water and dried with nitrogen.
[0066] The cleaned titanium metal plate was immersed in the sol solution for 5 seconds to ensure full contact between the sol solution and the titanium metal plate. The titanium metal plate was then slowly lifted at a speed of 0.5 cm / s, dried in air for 10 min, and then placed in a drying oven at 80°C for 10 min. After sintering, a 0.4 μm thick niobium pentoxide (Nb2O5) film was formed on the surface of the titanium metal plate to obtain the preform.
[0067] The above-mentioned preform was placed in a tube furnace and heated to 800°C at a rate of 10°C / min under the protection of argon. Then, NH3 with a partial pressure of 0.2MPa and a flow rate of 0.2L / min was introduced and nitrided at 800°C for 20min. Finally, a composite protective layer with a thickness of 1.4μm was formed on the surface of the titanium metal plate, and metal bipolar plate sample 1 was obtained.
[0068] The composite protective layer of sample 1 was analyzed using scanning electron microscopy, and the results are as follows: Figure 3 As shown, from Figure 3 It can be seen that the composite protective layer of sample 1 has a dense and crystalline morphology. Under 50,000x magnification, no porous structure that is detrimental to corrosion protection was found.
[0069] Elemental analysis of the composite protective layer of sample 1 was performed using scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), and the results are as follows: Figure 4 As shown, from Figure 4 As can be seen, the energy dispersive spectroscopy (EDS) results only show peaks for Ti, Nb, and N elements, with no peak for O. Therefore, it can be confirmed that the O element formed is Nb. x Ti y The solid solution contains nitrogen oxides. The stoichiometry calculated from the EDS peak area is shown in Table 1.
[0070] The composite protective layer of sample 1 was further analyzed using a TOF-SIMS 5 secondary ion mass spectrometer (TOF-SIMS) from IONTOF GmbH, Germany. The results are as follows: Figure 5 As shown, from Figure 5 It can be seen that the composite protective layer is mainly composed of NbN, TiN, and Ti2N, with titanium nitride (TiN / Ti2N) and niobium nitride (NbN) forming the doped layer. However, after 1200 seconds of etching, the NbN... + The signal (Counts<10) shows that the content of NbN decreases further away from the surface and is almost non-existent. That is, the bottom layer of the composite protective layer is a titanium nitride layer, and the top layer is a doped layer composed of titanium nitride (TiN / Ti2N) and niobium nitride (NbN).
[0071] The metal bipolar plate preparation method described in Example 1 was modified by changing some preparation conditions to obtain samples 2-8. The performance of samples 1-8 was tested, and the results are shown in Table 1. Among them, sample 0 is a titanium metal plate with a thickness of 0.1 mm made of TA1 grade industrial pure titanium.
[0072] Table 1
[0073]
[0074] First, comparing Sample 1 and Sample 2 in Table 1, it can be seen that the concentration of ethoxyniobium (Nb(OCH2CH3)5) sol solution is the main factor affecting the Nb content in the composite protective layer. However, the change in concentration has no significant effect on the contact resistance and corrosion resistance of the composite protective layer.
[0075] Secondly, comparing samples 2-4 and 6-7 in Table 1, it can be seen that the nitriding temperature has a decisive influence on the performance of the composite protective layer. However, after 800℃, the performance has reached a plateau, and the changes brought about by increasing the nitriding temperature are no longer significant. Moreover, when the nitriding temperature continues to rise to 850℃, the samples have already shown obvious curling, indicating that when approaching the titanium α→β phase transformation temperature (882.5℃), the deformation risk caused by hot working is no longer negligible.
[0076] Furthermore, comparing samples 2 and 5 in Table 1, it can be seen that nitriding time also affects the contact resistance and corrosion resistance of the composite protective layer. After nitriding for 20 minutes, the contact resistance and acid corrosion resistance no longer change significantly.
[0077] As shown in Table 1, the contact resistance of samples 1-5 initially showed excellent performance. Therefore, samples 1-5 were further anodized at 0.6V for 24h and their contact resistance was tested. The results are shown in Table 2.
[0078] Table 2
[0079] Sample 0.6V anodization for 24h contact resistance @ 140N / cm 2 (mΩ / cm 2 )]]> 0 472.8 1 5.9 2 6.25 3 5.5 4 8.2 5 5.4
[0080] As shown in Table 2, after 24 hours of anodizing at 0.6V, the contact resistance of samples 1-5 only increased slightly and remained less than 10 mΩ / cm. 2 This favorable range therefore offers a significant advantage in mitigating the high contact resistance caused by anodizing.
[0081] Example 2
[0082] First, add 58.3 mL of anhydrous ethanol to a flask. Under magnetic stirring, slowly add 3.2 g of vanadium trichloride (VCl3) powder, followed by slowly adding 1.35 mL of deionized water and 0.33 mL of concentrated nitric acid (HNO3 concentration 63%). After the addition is complete, the solution turns dark green. Then, gradually raise the temperature to 60°C and maintain the temperature under reflux for 3 hours to allow the materials to react completely, resulting in a dark green transparent liquid. After aging at room temperature for one day, a sol solution is obtained.
[0083] The selection of titanium metal plates and the cleaning steps are the same as in Example 1.
[0084] The cleaned titanium metal plate was immersed in the above-mentioned sol solution for 5 seconds to ensure full contact between the sol solution and the titanium metal plate. Then, the titanium metal plate was slowly lifted at a speed of 0.5 cm / s, dried in air for 10 min, and then placed in a drying oven at 80°C for 10 min. After that, sintering was performed to form a vanadium pentoxide (V2O5) film with a thickness of 0.5 μm on the surface of the titanium metal plate, thus obtaining the preform.
[0085] The aforementioned preform was placed in a tube furnace and heated to 700°C at a rate of 10°C / min under argon protection. Then, NH3 with a partial pressure of 0.2 MPa and a flow rate of 0.5 L / min was introduced and maintained for 120 min, ultimately forming a 1.2 μm thick composite protective layer (V) on the surface of the titanium metal plate. 0.12 Ti 1.64 N), to obtain a metal bipolar plate sample.
[0086] The composite protective layer obtained in this embodiment was analyzed using a scanning electron microscope, and the results are as follows: Figure 6 As shown, from Figure 6 It can be seen that the composite protective layer obtained in this embodiment has almost the same morphology as that of sample 1. Both exhibit a dense morphology and are crystalline. Under 50,000x magnification, no porous structure that is detrimental to corrosion prevention was found.
[0087] After testing, the contact resistance of the composite protective layer obtained in this embodiment was 3.6 mΩ / cm. 2 Its natural corrosion current density is 0.08 μA / cm. 2 The passivation current density at 0.6V for 24 hours is 0.05μA / cm. 2 It has excellent electrical conductivity and corrosion resistance.
[0088] Example 3
[0089] First, add 58.3 mL of anhydrous ethanol to a flask. Under magnetic stirring, slowly add 7.3 g of tantalum pentachloride (TaCl5) powder, followed by slowly adding 1.35 mL of deionized water and 0.33 mL of concentrated nitric acid (HNO3 concentration 63%). After the addition is complete, the solution becomes transparent. Then, gradually raise the temperature to 60°C and maintain the temperature under reflux for 3 hours to allow the materials to react completely, obtaining a colorless, transparent liquid. Aging at room temperature for one day yields a sol solution.
[0090] The selection of titanium metal plates and the cleaning, immersion coating, and nitriding processes were the same as those for sample 2 in Example 1.
[0091] The composite protective layer obtained in this embodiment was analyzed using a scanning electron microscope, and the results are as follows: Figure 7 As shown, from Figure 7 It can be seen that the composite protective layer obtained in this embodiment has almost the same morphology as that of sample 1. Both exhibit a dense morphology and are crystalline. Under 50,000x magnification, no porous structure that is detrimental to corrosion prevention was found.
[0092] After testing, the composite protective layer (Ta) obtained in this embodiment was found to be... 0.11 Ti 1.65 The contact resistance of N) is 6.25 mΩ / cm. 2 Its natural corrosion current density is 0.015 μA / cm. 2 The passivation current density at 0.6V for 24 hours is 0.01μA / cm. 2 It exhibits excellent electrical conductivity and corrosion resistance. Furthermore, the contact resistance after anodizing at 0.6V for 24 hours is 7.3 mΩ / cm. 2 It exhibits excellent durability under long-term operating conditions.
[0093] Example 4
[0094] The difference between Example 4 and Example 1 is that an Nb2O5 thin film was prepared on one side of a titanium metal plate using a spraying method. The specific spraying process is as follows:
[0095] The sol solution was poured into the spray gun's tank, and the cleaned titanium sheet was secured. A 0.02mm diameter nozzle was selected to ensure a single spray width of less than 8mm. The spray gun pressure was set to 0.5MPa, and spraying began. After spraying, the sheet was air-dried for 10 minutes and then placed in an 80℃ drying oven for another 10 minutes. Sintering was then performed to form a 0.4μm thick niobium pentoxide (Nb₂O₅) film on the surface of the titanium sheet, resulting in the preform.
[0096] After testing, the contact resistance of the composite protective layer obtained in this embodiment was 4.6 mΩ / cm.2 Its natural corrosion current density is 0.02 μA / cm. 2 The passivation current density at 0.6V for 24 hours is 0.025 μA / cm. 2 It has excellent electrical conductivity and corrosion resistance.
[0097] In the above examples and comparative examples, the test methods for contact resistance and corrosion electrochemistry are as follows:
[0098] Contact resistance test: The contact resistance was determined using the method shown in GB / T 20042.6-2011. The sample was tested using an FT-341SJB bipolar plate contact resistance tester from Ningbo Ruike Weiye Instrument Co., Ltd. The carbon paper used to simulate the gas diffusion layer was hydrophobic carbon paper (TGP-H-060) manufactured by Toray Industries. During the test, the resistance of the actual test system was first calibrated using a single sheet of carbon paper according to GB / T20042.7-2014, including the contact resistance between the carbon paper and the gold electrode surface and the carbon paper's own resistance, to obtain R1. Then, two sheets of carbon paper were sandwiched between the test sample, and the same contact resistance test was performed to obtain R2. Since the bulk resistance of the test sample is negligible, the contact resistance of the sample can be calculated using R = (R2 - R1) / 2. In this test, the conductivity of the composite protective layer was 140 N / cm. 2 Less than 10 mΩ / cm under pressure 2 Good; if it exceeds 10 mΩ / cm 2 That would be considered bad.
[0099] Corrosion electrochemical testing: The testing methods refer to both the national standard GB / T 20042.6-2011 and the evaluation method based on corrosion current density in the DOE Technical Targets for Polymer Electrolyte Membrane Fuel Cell Components recommended by the U.S. Department of Energy. The sample was first tested using a potentiodynamic scanning method to determine the natural corrosion current density.
[0100] Before testing, the sample was processed into a 1.5 cm diameter disc and, after being cleaned with ethanol and deionized water, was mounted on the working electrode for electrochemical testing, with an effective testing area of 1 cm². 2 A conventional three-electrode system, comprising a working electrode, an Ag / AgCl reference electrode, and a platinum counter electrode, was connected to an electrochemical workstation (CHI600E, CH Instruments Ins) via wires. The corrosion environment for the potentiodynamic scanning was set to 80°C, pH 3, and containing 0.1 ppm F. -A sulfuric acid solution was used. Before the potentiodynamic scanning, air was removed from the solution by argon gas purging, followed by a 30-minute open-circuit voltage (OCP) test. The change in open-circuit voltage within 100 seconds was required to ensure a near-steady-state condition. The potentiodynamic scanning rate was set to 1 mV / s, with a scanning range of -0.4 V to 0.6 V. After the scan, the polarization curve was obtained, and the natural corrosion current density at the natural corrosion potential was calculated using Tafel extrapolation. In this test, the natural corrosion current density of the sample was less than 1.0 μA / cm². 2 Good; if it exceeds 1.0 μA / cm 2 That would be considered bad.
[0101] Subsequently, a 0.6V constant potential scan was performed to simulate the corrosion environment of anodic oxidation under actual working conditions. The constant potential scan was conducted for 24 hours under air-filled conditions at a constant voltage of 0.6V, with an air flow rate of 20 mL / min. The remaining corrosion environment was the same as that of the potentiodynamic scan. Due to the considerable evaporation of the solution during the long-term test at 80℃, the acidity and F content increased in the later stages of the experiment. - The concentration increased. A peristaltic pump was used to replenish deionized water throughout the test to ensure a consistent solution volume; the replenishment volume was determined through prior experiments. The final passivation corrosion current density was obtained at the end of the test. In this test, the passivation corrosion current density of the sample was less than 0.05 μA / cm². 2 Good; if it exceeds 0.05 μA / cm 2 That would be considered bad.
[0102] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0103] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A metal bipolar plate, characterized in that, include: Titanium metal plate; A composite protective layer is disposed on the surface of the titanium metal plate. The composite protective layer includes group VB transition metal nitrides and titanium nitride, and the group VB transition metal nitrides and titanium nitrides are doped with the chemical formula M. x Ti y The titanium nitride is a solid solution of N, where M represents a group VB transition metal element, and 0.01≤x≤0.15, 1.60≤y≤2.
00. The titanium nitride is formed by the diffusion and reaction of titanium atoms in the titanium metal plate.
2. The metal bipolar plate according to claim 1, characterized in that, The group VB transition metal nitrides are selected from at least one of vanadium nitride, niobium nitride, or tantalum nitride.
3. The metal bipolar plate according to claim 1, characterized in that, The microstructure of the composite protective layer is crystalline.
4. The metal bipolar plate according to claim 1, characterized in that, The composite protective layer includes a bottom layer and a top layer, the bottom layer being located between the titanium metal plate and the top layer, and the mass fraction of the group VB transition metal nitride in the top layer being greater than the mass fraction in the bottom layer.
5. The metal bipolar plate according to claim 4, characterized in that, The bottom layer is a titanium nitride layer, and the top layer is a doped layer of the group VB transition metal nitride and the titanium nitride.
6. The metal bipolar plate according to claim 1, characterized in that, The thickness of the titanium metal plate is ≤0.5mm; And / or, the thickness of the composite protective layer is 0.4μm-1.5μm.
7. A method for preparing a metal bipolar plate as described in any one of claims 1-6, characterized in that, Includes the following steps: Titanium metal sheets are available; A group VB transition metal oxide thin film is prepared on the surface of the titanium metal plate to obtain a preform; The preform is nitrided at a temperature of 700℃-825℃ to obtain a metal bipolar plate.
8. The method for preparing a metal bipolar plate according to claim 7, characterized in that, A group VB transition metal oxide film with a thickness of 0.1 μm to 0.7 μm was prepared on the surface of the titanium metal plate by a sol-gel method.
9. The method for preparing a metal bipolar plate according to claim 7, characterized in that, The medium for nitriding is nitrogen-containing gas or a mixture of nitrogen-containing gas and a protective gas.
10. The method for preparing a metal bipolar plate according to claim 9, characterized in that, The flow rate of the nitrogen-containing gas is 0.1 L / min to 1.0 L / min, and the pressure is 0.2 MPa to 0.5 MPa.
11. The method for preparing a metal bipolar plate according to claim 9 or 10, characterized in that, The nitrogen-containing gas is selected from at least one of NH3 and N2.
12. An application of a metal bipolar plate as described in any one of claims 1-6 in a fuel cell.
Citation Information
Patent Citations
Fuel cell component having a durable conductive and hydrophilic coating
CN1953259A
TiN coating surface modified titanium alloy bipolar plate and liquid ion nitriding method thereof
CN112467161A
Layer system for coating a bipolar plate, bipolar plate, and fuel cell
CN113892204A
